Activities in adolescence: Optimal experiences and self-perceptions - Calero, Alejandra Daniela (2016)
The objective of this study was to compare the levels of optimal experiences (OE) that adolescents report in different activities of the school and out-of-school context and to analyze how these levels are related to self-concept and self- esteem in the adolescent population at Autonomous City of Buenos Aires, Argentina (ACBA-AR). For this purpose, the OE Brief Inventory and the Self-Perception Profile were administered to 399 adolescents attending ACBA-AR high schools. We performed an ANOVA with repeated measures with intrasubject main effect to compare the OEs in each activity and a correlation analysis to study the relationship between OE and self-concept and self-esteem. Among the results, we found that adolescents experience higher levels of occurrence of OE in extracurricular activities. With regard to self-concept and self-esteem, the relationships found were in all cases positive and showed differences according to the type of activity in which OE were reported.